Thermogravimetric study of the Tungsten-Oxygen system in the Range 2.89 < 0/W < 3.00 between 1023 and 1223 K - Caneiro, Alberto (Comisión Nacional de Energía Atómica; Argentina)
Fil: Caneiro, Alberto Comisión Nacional de Energía Atómica; Argentina